LAND-COVER MODELLING USING CORINE LAND COVER DATA AND MULTI-LAYER PERCEPTRON - Dzieszko, Piotr (Quaestiones Geographicae, 2014)
Last decades of research have revealed the environmental impacts of Land-Use/Cover Change (LUCC) throughout the globe. Human activities’ impact is becoming more and more pronounced on the natural environment. The key activity in the LUCC projects has been to simulate the syntheses of knowledge of LUCC processes, and in particular to advance understanding of the causes of land-cover change. Still, there is a need of developing case studies regional models to understand LUCC change patterns. The aim of this work is to reveal and describe the main changes in LUCC patterns occurring in Poznań Lakeland Mesoregion according to CORINE Land Cover database. Change analysis was the basis for the identification of the main drivers in land cover changes in the study area. The dominant transitions that can be grouped and modelled separately were identified. Each submodel was combined with all submodels in the final change prediction process. Driver variables were used to model the historical change process. Transitions were modelled using multi-layer perceptron (MLP) method. Using the historical rates of change and the transition potential model scenario for year 2006 was predicted. Corine Land Cover 2006 database was used for model validation.